Scientific and academic production and visibility of the Faculty of Health Sciences of Universidad del Cauca. - Quilindo, Catalina; Calvache, José Andrés; Delgado-Noguera, Mario (Revista Facultad de Medicina de la Universidad Nacional de Colombia, 2018)
Introduction: Bibliometric indexes are important indicators of the quality of the country's medical programs. There are few studies of this kind at the Universidad del Cauca. Objective: To evaluate the scientific-academic activity of the Faculty of Health Sciences (FHS) of the Universidad del Cauca based on bibliometric production indicators of the authors, visibility and impact during the period 2010-2016. Materials and methods: Descriptive, cross-sectional, bibliometric research. Different categories of the academic production of the FHS were identified (citation by authors, language of publication, areas of health sciences), and the main journals where the authors published. In addition, the metric indicators of the journals and citation indexes of the authors were determined, as well as their enrollment in research groups and the most cited publications according to SCOPUS. Results: 183 articles were found. The main language of publication was Spanish and mainly in the clinical-surgical area. 60% of the articles of the main authors have some international collaboration. The Revista de la Facultad de Ciencias de la Salud of Universidad del Cauca had the largest number of articles published by authors of the same faculty during the period under study. Conclusion: The scientific and academic production and visibility of the FHS of the Universidad del Cauca is low. The findings reveal the need for greater institutional support for research, and the creation and support of research groups and incubators. Therefore, this work seeks to encourage greater visibility of the FHS in the national and international scientific field.